The Role Of Parental Upbringing In The Emotional Social Of Young Children Through Traditional Games In The Village Of Dukuh dempok, Wuluhan District, Jember District - Ula Yulia Asari, Rahmatul; Ulul Azmi, Hoiriyah; Munawaroh, Zahrotul; Eky, Prasetya Pertiwi; Hendrik , Siswono; Priawasana, Endra (Journal of Education Technology and Inovation, 2023)
The aim of this research is to preserve the traditional game cublak-cublak suweng as an effort to divert children's attention from gadget addiction in the form of the role of parenting in Dukuh Dempok Village. In Dukuh Dempok Village, there are problems experienced by young children, namely that the majority of young children there have experienced a lack of social interaction between early childhood with their parents and the surrounding environment, including their peers, where children play with gadgets more often and this results in lack of obedience to parental orders. The role of effective parenting is like the role of parenting in the family, which means the habits of parents in leading, nurturing and guiding children in the family. Nurturing means taking care of it by caring for it, educating it, guiding it by helping it, and training it in all things. Because every child has the right to receive growth and development that is appropriate to his or her stage of development. Through traditional games, the role of parents is very necessary to encourage children's social emotional development, especially children's social interactions. The type of research method used is descriptive qualitative. This research was located in Dukuh Dempok Village, Wuluhan District, Jember Regency. Based on the research results, it can be concluded that the role of parental parenting in Dukuh Dempok Village through the traditional game cublak-cublak suweng influences social interactions and can instill character education in early childhood. In line with this, the role of parenting provided by parents (especially mothers) in Dukuh Dempok Village towards early childhood is: a). The role of parents as companions, b). The role of parents as financial support, and c). The role of parents as Preservers of Traditional Culture